(untitled) (TEL Tempo, Espaço e Linguagem, 2019)
O presente artigo compõe uma pesquisa de mestrado e concerne à análise da coleção de fotografias de boxe da Federação Paranaense de Pugilismo (FPP), que está circunscrita as décadas de 1960 e 2000. A partir da mesma coleção, representações pugilísticas foram historicamente problematizadas e associadas ao conceito de violência sob a ótica do processo civilizatório de Norbert Elias. Abstract: This paper composes a master’s research and concerns the analysis of a photographical collection about boxing. Circumscribed among the 1960’s and the 2000’s, it belongs to the Pugilism Federation of Paraná. Through the same collection, pugilistic representations were historically problematized and associated to the conception of violence by the optic of the civilizing process, by Norbert Elias. Keywords: Boxing history. Photographs. Pugilistic representations. Civilizing process. Violence. Resumen: El presente artículo compone una pesquisa de maestría e se refiere a una analisis hecha en una colección de fotografias del boxeo de La Federación Paranaense del Pugilismo (FPP), que esta circunscrito entre los años de 1960 y 2000. Por medio de la misma colección, representaciones del boxeo fueron historicamente problematizados y asociados al concepto de violencia bajo la perspectiva del proceso civilizatorio de Norbet Elias. Palabras clave: Historia del Boxeo. Fotografias. Representaciones pugilisticas. Proceso civilizatório. Violencia.